Effect of Good Perception, Awareness, and Willingness Pay Tax to Compliance Taxpayers (Case Studies at KPP Pratama Bandung Karees) - Azzam, Ubaydillah; Zen, Tuntun Salamatun (Journal of Business and Management, 2015)
Abstract. Receipt of funds in the country is a very important aspect for the State to run the government. Without funding, the State would be very difficult to develop development or welfare of its people. One of the national income originating in the country is a tax. Tax issues in Indonesia have reached the stage of a very chronic. The high demand for income countries is not supported by increasing public awareness of tax payment. Many factors lead to a tax problem in Indonesia. A good perception of effectiveness system tax, willingness to pay tax, and awareness to pay tax are factors that studied in this research. Tools that use in this research are multiple linear regression analysis, F test, and coefficient of determination. Conclusion of this research is that all variables in this research are correlated.Â Keywords: Tax, Income tax, Awareness, Willingness, A good perception of system pay tax